Understanding American Values Through Emerson’s Self-Reliance - Rudy Rudy (IdeBahasa, 2019)
The study focuses on the influence of one of the prominent figures in American romanticism, Ralph Emerson. By applying the Hall’s Theory of Representation this study intends to identify the role of Self-Reliance in American culture and the impact of Emerson’s philosophy toward American life And now people all over the world have recognized his work Self-Reliance (1841) as the inspiration in many aspects of life. His hard work, ethical teaching and spirit have become the most important ideas in shaping independent American society. Through his literary works, Emerson has conveyed important messages to the world on shaping personalities.